Ilusyon - Villanueva, Paolo; Ramos, Ellen; Digital Viva Films (Firm). (Quezon City Digital Viva Films, 2005)
Set in 1958, Ilusyon tells the story of Miguel, a young man from the countryside, who decide to visit his father, Pablo, a modernist painter in Manila. Upon his arrival, he discovers that his father has decided to leave for the province to heal from depression after the recent death of his wife and Miquel's mother. Miguel opts to stay in Manila for a vacation - where he finds a job as a house painter and realizes the city life might fit him well. One day, he meets Stella, a nude model originally scheduled for pose for Miguel's father. Struck by her beauty, Miguel does the unthinkable - he pretends to be his father. He pretends to paint her and hides his doodles from the unwitting Stella. Developing a relationship based on a lie, things turn for the worse when Stella begets a strange skin disease that turns off Miguel. Surrounded by strange characters. Miguel is driven into a frenzied realization about beauty, lust, love, and being true to one's self.
DVD
executive producer Vic Del Rosario, story and screenplay by John Red, directed by Paolo Villanueva and Ellen Ramos.
Keywords: Feature Films